Advancements in Laser and Optoelectronics Engineering for Medical Applications: Current Trends and Future Prospects - Habib, Rusul Hadi Mohammed; Isaa, Nisreen Adel Mohammed; Farag, Hasna Haitham Ayed; Abdel-Sayed, Maryam Jabbar Obeid; Jaafar, Asraa Ali Muhammad (American Journal of Botany and Bioengineering, 2025)
Laser and optoelectronics engineering have revolutionized medical applications, offering innovative solutions for diagnostics, imaging, and therapeutic procedures. Despite significant advancements, there remains a knowledge gap in integrating these technologies into mainstream clinical practice. This study employs a comprehensive review of emerging laser-based techniques, optoelectronic sensor applications, and their implications for personalized medicine. Findings indicate that advancements in laser precision and optical imaging have improved early disease detection and non-invasive treatments, with significant benefits in ophthalmology, oncology, and neurosurgery. The results underscore the potential of these technologies in enhancing healthcare efficiency, reducing procedural risks, and advancing minimally invasive medical interventions.